The university is a cultural scientific system (Research in social anthropology (Journal of the College of Basic Education, 2022)
Countries with their universities, as they say, because the university is the carrier of scientific culture for successive generations, and the owner of scientific development and progress in any country. Therefore, attention must be directed to it and given what it needs in order to continue creativity, innovation, development of science and production of a generation loaded with scientific ideas that are able to keep pace with global developments.